2020
DOI: 10.23818/limn.39.27
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the use of molecular tools in ecological and biodiversity assessment of aquatic ecosystems

Abstract: Advances in the use of molecular tools in ecological and biodiversity assessment of aquatic ecosystemsConservation and sustainable management of aquatic ecosystems is a priority in environmental programs worldwide. However, these aims are highly dependent on the efficiency, accuracy and cost of existent methods for the detection of keystone species and monitoring of biological communities. Rapid advances in eDNA, barcoding and metabarcoding promoted by high-throughput sequencing technologies are generating mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Spatial and temporal variation in environmental variables affected the distribution of diatom assemblages in the current study, which is in agreement with findings of ecological studies (Feio et al, 2020; Freitas et al, 2021). Results of ANOSIM indicated that there was no significant difference in the diatom composition of Değirmendere and Bulaklı streams among sampling seasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Spatial and temporal variation in environmental variables affected the distribution of diatom assemblages in the current study, which is in agreement with findings of ecological studies (Feio et al, 2020; Freitas et al, 2021). Results of ANOSIM indicated that there was no significant difference in the diatom composition of Değirmendere and Bulaklı streams among sampling seasons.…”
Section: Discussionsupporting
confidence: 93%
“…Spatial and temporal variation in environmental variables affected the distribution of diatom assemblages in the current study, which is in agreement with findings of ecological studies (Feio et al, 2020;Freitas et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, efforts have been undertaken to integrate metabarcoding in freshwater monitoring (Elbrecht & Steinke, 2019;Feio et al, 2020;Leese et al, 2016;Pawlowski et al, 2018), which for organisms such as diatoms have succeeded in producing methods that are virtually ready for practical application (Apothéloz-Perret-Gentil et al, 2017;Cordier, Lanzén, Apothéloz-Perret-Gentil, Stoeck, & Pawlowski, 2019;Mortágua et al, 2019;Visco et al, 2015), whereas for others, a great deal of optimization and standardization is still needed (Pawlowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, it was demonstrated that these constraints can at least partly be offset by molecular techniques such as DNA metabarcoding, which allows the identification of multiple taxa from environmental samples using standard genetic markers (Baird & Hajibabaei, 2012; Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012). Consequently, efforts have been undertaken to integrate metabarcoding in freshwater monitoring (Elbrecht & Steinke, 2019; Feio et al., 2020; Leese et al., 2016; Pawlowski et al., 2018), which for organisms such as diatoms have succeeded in producing methods that are virtually ready for practical application (Apothéloz‐Perret‐Gentil et al., 2017; Cordier, Lanzén, Apothéloz‐Perret‐Gentil, Stoeck, & Pawlowski, 2019; Mortágua et al, 2019; Visco et al., 2015), whereas for others, a great deal of optimization and standardization is still needed (Pawlowski et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new and accurate DNA-based biomonitoring methodologies are currently being developed using species-level DNA barcodes (e.g., Elbrecht et al 2017;Blackman et al 2019;Martins et al 2019). Even phylogenetic (Zhou et al 2016;Thomas et al 2020) and biodiversity conservation studies (e.g., Ruppert et al 2019;Feio et al 2020) can benefit from these DNA sequencing techniques.…”
Section: Introductionmentioning
confidence: 99%